Phytoecdysteroids Accelerate Recovery of Skeletal Muscle Function Following in vivo Eccentric Contraction-Induced Injury in Adult and Old Mice - Zwetsloot, Kevin A.; Shanely, R. Andrew; Godwin, Joshua S.; Hodgman, Charles F. (Frontiers in Rehabilitation Sciences, 2021)
Background: Eccentric muscle contractions are commonly used in exercise regimens, as well as in rehabilitation as a treatment against muscle atrophy and weakness. If repeated multiple times, eccentric contractions may result in skeletal muscle injury and loss of function. Skeletal muscle possesses the remarkable ability to repair and regenerate after an injury or damage; however, this ability is impaired with aging. Phytoecdysteroids are natural plant steroids that possess medicinal, pharmacological, and biological properties, with no adverse side effects in mammals. Previous research has demonstrated that administration of phytoecdysteroids, such as 20-hydroxyecdysone (20E), leads to an increase in protein synthesis signaling and skeletal muscle strength. Methods: To investigate whether 20E enhances skeletal muscle recovery from eccentric contraction-induced damage, adult (7-8 mo) and old (26-27 mo) mice were subjected to injurious eccentric contractions (EC), followed by 20E or placebo (PLA) supplementation for 7 days. Contractile function via torque-frequency relationships (TF) was measured three times in each mouse: pre- and post-EC, as well as after the 7-day recovery period. Mice were anesthetized with isoflurane and then electrically-stimulated isometric contractions were performed to obtain in vivo muscle function of the anterior crural muscle group before injury (pre), followed by 150 EC, and then again post-injury (post). Following recovery from anesthesia, mice received either 20E (50 mg•kg-1 BW) or PLA by oral gavage. Mice were gavaged daily for 6 days and on day 7, the TF relationship was reassessed (7-day). Results: EC resulted in significant reductions of muscle function post-injury, regardless of age or treatment condition (p<0.001). 20E supplementation completely recovered muscle function after 7 days in both adult and old mice (pre vs. 7-day; p>0.05), while PLA muscle function remained reduced (pre vs 7-day; p<0.01). In addition, histological markers of muscle damage appear lower in damaged muscle from 20E-treated mice after the 7-day recovery period, compared to PLA. Conclusions: Taken together, these findings demonstrate that 20E fully recovers skeletal muscle function in both adult and old mice just 7 days after eccentric contraction-induced damage. However, the underlying mechanics by which 20E contributes to the accelerated recovery from muscle damage warrant further investigation.